Causality of Blood Metabolites on Proliferative Diabetic Retinopathy: Insights From a Genetic Perspective - Zhaoxiang Wang; Bing Lu; Li Zhang; Yuwen Xia; Xiaoping Shao; Shao Zhong (Journal of Diabetes Research)
Conclusion: These metabolites have the potential to be used as biomarkers and are promising for future research into the mechanisms and drug targets for PDR.